Short-term heat exposure affects thermogenesis and mitophagy in goat brown adipocytes - Yulong Song; Die Li; Duo Su; Tingting Jiang; Longrui Li; Siyuan Zhan; Tao Zhong; Jiazhong Guo; Jiaxue Cao; Li Li; Hongping Zhang; Linjie Wang (BMC Genomics)
Abstract Background Brown adipose tissue (BAT) has a significant impact in newborn goats on maintaining body temperature through non-shivering thermogenesis in response to cold exposure. However, the roles of heat treatment on BAT thermogenesis are still limited. Results This study focused on the effects of short-term heat exposure on goat brown adipocytes. We found that the content of mitochondria and the proteins of UCP1 and PGC1α were increased after 12 h of heat exposure. Additionally, the triglyceride (TG) content was significantly decreased after 1, 2, 6 h of heat exposure. Furthermore, RNA-seq analysis of brown adipocytes after 12 h of heat exposure identified 1091 differentially expressed genes (DEGs). The KEGG enrichment analysis were mainly enriched in thermogenesis, fatty acid metabolism and mitophagy. In addition, we found that the amount of mitophagosomes and expression levels of mitophagy-related protein (LC3BII/LC3BI, BNIP3, and BECN) were elevated after 12 h of heat treatment. Conclusion These findings collectively indicate that heat exposure enhances the thermogenic capacity and mitophagy level of goat brown adipocytes. Our study provides evidence that heat exposure facilitates adaptive thermogenesis in goat brown adipocytes.